THE BEST SMART RESEARCH: INTELLIGENCE SHAPING THE FUTURE OF MEDICINE - Zokirjonova Havasxon Mahammadjon qizi; Tursunmetov Ibodulla Roʻzibayevich (TADQIQOTLAR, 2025)
This article highlights the most relevant and advanced smart research in 21st- century medicine. It analyzes innovations in healthcare through artificial intelligence (AI), smart medical devices, genomics, neurotechnologies, and modern technologies applied in medical education. The article presents positive changes such as early disease detection, the creation of personalized treatment plans, and new opportunities for paralyzed patients using AI. It also predicts the role of smart clinics and robotic surgeons in the future. These advancements bring great opportunities and responsibilities for modern physicians.